RISING METHANE GAS BUBBLES FORM MASSIVE HYDRATE LAYERS AT THE SEAFLOOR - Haeckel M.; Suess E.; Wallmann K.; Rickert D. (My University, 2004)
Extensive methane hydrate layers are formed in the near-surface sediments of the Cascadia margin. An undissociated section of such a layer was recovered at the base of a gravity core (i.e. at a sediment depth of 120 cm) at the southern summit of Hydrate Ridge. As a result of salt exclusion during methane hydrate formation, the associated pore waters show a highly elevated chloride concentration of 809 mM. In comparison, the average background value is 543 mM.A simple transport-reaction model was developed to reproduce the Cl− observations and quantify processes such as hydrate formation, methane demand, and fluid flow. From this first field observation of a positive Cl− anomaly, high hydrate formation rates (0.15–1.08 mol cm−2 a−1) were calculated. Our model results also suggest that the fluid flow rate at the Cascadia accretionary margin is constrained to 45–300 cm a−1. The amount of methane needed to build up enough methane hydrate to produce the observed chloride enrichment exceeds the methane solubility in pore water. Thus, most of the gas hydrate was most likely formed from ascending methane gas bubbles rather than solely from CH4 dissolved in the pore water.